Mechanism of CK2 Inhibition by a Ruthenium-Based Polyoxometalate - Fabbian, Simone; Giachin, Gabriele; Bellanda, Massimo; Borgo, Christian; Ruzzene, Maria; Spuri, Giacomo; Campofelice, Ambra; Veneziano, Laura; Bonchio, Marcella; Carraro, Mauro; Battistutta, Roberto (Frontiers in Molecular Biosciences, 2022)
CK2 is a Ser/Thr protein kinase involved in many cellular processes such as gene expression, cell cycle progression, cell growth and differentiation, embryogenesis and apoptosis. Aberrantly high CK2 activity is widely documented in cancer, but the enzyme is also involved in several other pathologies, such as diabetes, inflammation, neurodegeneration and viral infections, including COVID-19. Over the last years, a large number of small-molecules able to inhibit the CK2 activity have been reported, mostly acting with an ATP-competitive mechanism. Polyoxometalates (POMs), are metal-oxide polyanionic clusters of various structures and dimensions, with unique chemical and physical properties. POMs were identified as nanomolar CK2 inhibitors, but their mechanism of inhibition and CK2 binding site remained elusive. Here, we present the biochemical and biophysical characterizing of the interaction of CK2α with a ruthenium-based polyoxometalate, [Ru4(μ-OH)2(μ-O)4(H2O)4 (γ-SiW10O36)2]10− (Ru4POM), a potent inhibitor of CK2. Using analytical SEC, ITC and SAXS we were able to unravel the mechanism of inhibition of Ru4POM. Ru4POM binds to the positively-charged substrate binding region of the enzyme through electrostatic interactions, triggering the dimerization of the enzyme which consequently is inactivated. Ru4POM is the first non-peptide molecule showing a substrate-competitive mechanism of inhibition for CK2. On the basis of SAXS data, a structural model of the inactivated (CK2α)2(Ru4POM)2 complex is presented.